Sister of P-glycoprotein expression in different tissues - Török, Michael; Gutmann, Heike; Fricker, Gert; Drewe, Jürgen (Biochemical pharmacology, 1999)
Sister of P-glycoprotein (spgp) is a gene that is closely related to the P-glycoprotein family (Pgps). This class of proteins belongs to the superfamily of ATP-binding cassette transporters and is known for its involvement in pharmacological drug interactions. Therefore, this study investigated the distribution of spgp expression in different tissues known for their high levels of Pgps expression such as brain, liver, kidney, small- and large-gut mucosa. Analysis was done by using the reverse transcription-polymerase chain reaction. In addition to a high expression in the liver, we were able to demonstrate a significant spgp expression in brain grey cortex, small- and large-gut mucosa. Although Pgps are expressed in the kidney and brain capillary endothelial cells, no expression of spgp was detected in these tissues, which might indicate that spgp has no function in the blood-brain barrier and is not involved in the renal excretion of drugs.
Gesehen am 26.04.2017